Passive heating system to achieve termal comfort in high Andean homes in Perú - Cerron Contreras, Amanda (2022)
The present research aims to provide updated information on passive heating systems in Perú and to establish which are the most optimal passive heating strategies that have achieved an improvement in indoor thermal comfort in high Andean homes. A review of articles from the scientific literature specialized in the area of passive heating systems applied to high Andean homes in the highlands of Peru that are located within the range of 3 000 to 5 000 meters above sea level, which are characterized by having a cold climate and also be exposed to the problem of frosts typical of these places. The results of these articles show that the most efficient passive heating systems or strategies achieved an increase in the interior temperature by 9.5°C on average, not being enough to achieve thermal comfort in high Andean homes, but that they are favorable because they achieve improve the feeling of well-being of users.